SISTEM INFORMASI MANAJEMEAN SURAT BERBASIS WEB DAN MOBILE (STUDI KASUS SMK NURUL HUDA RABASAN CAMPLONG) - Imam Syafi’i; Nafisah Nafisah; Idon Joni (Insand Comtech : Information Science and Computer Technology Journal, 2021)
Information technology is currently growing rapidly, so that causing all aspects of human life are always associated with the development of these technologies. The influence of these technological developments can be felt by various fields both from the academic and non-academic fields. The benefits that can be felt from technological developments are data processing that can be done precisely, quickly, and accurately. With the help of information technology, all data processing in the system can be done in various different places so that it can be more effective and efficient. Educational institutions or companies every day must carry out the activities of managing letters. Good management of letters will make it easier for educational institutions or companies, and vice versa letters that are not managed properly will have a negative impact on educational institutions or companies. The information contained in the letter is an important asset for educational institutions or companies to carry out various activities, for example incoming and outgoing letters. Therefore the letter needs to be managed properly so that the maximum for the smooth achievement of the goals of educational institutions or companies. As for the constraints in managing incoming and outgoing letters such as disposition data, in the disposition data the TU officer prints disposition sheets after being printed and is submitted to the principal to be filled in after being returned returned to the TU officer to be added, and the TU Officer cannot make outgoing mail data only save mail data only.Keywords: Application, Prototype, Technology.